Cholinergic Modulation of the Immune System Presents New Approaches for Treating Inflammation - Hoover, Donald B. (Pharmacol Ther, 2017)
The nervous system and immune system have broad and overlapping distributions in the body, and interactions of these ubiquitous systems are central to the field of neuroimmunology. Over the past two decades, there has been explosive growth in our understanding of neuroanatomical, cellular, and molecular mechanisms that mediate central modulation of immune functions through the autonomic nervous system. A major catalyst for growth in this field was the discovery that vagal nerve stimulation (VNS) caused a prominent attenuation of the systemic inflammatory response evoked by endotoxin in experimental animals. This effect was mediated by acetylcholine (ACh) stimulation of nicotinic receptors on splenic macrophages. Hence, the circuit was dubbed the “cholinergic anti-inflammatory pathway”. Subsequent work identified the α7 nicotinic ACh receptor (α7nAChR) as the crucial target for attenuation of pro-inflammatory cytokine release from macrophages and dendritic cells. Further investigation made the important discovery that cholinergic T cells within the spleen and not cholinergic nerve cells were the source of ACh that stimulated α7 receptors on splenic macrophages. Given the important role that inflammation plays in numerous disease processes, cholinergic anti-inflammatory mechanisms are under intensive investigation from a basic science perspective and in translational studies of animal models of diseases such as inflammatory bowel disease and rheumatoid arthritis. This basic work has already fostered several clinical trials examining the efficacy of VNS and cholinergic therapeutics in human inflammatory diseases. This review provides an overview of basic and translational aspects of the cholinergic anti-inflammatory response and relevant pharmacology of drugs acting at the α7nAChR.